KAJIAN LITERATUR DESAIN UI/UX APLIKASI MOBILE UNTUK MANAJEMEN KONTROL KEHAMILAN (Teknosia, 2024)
The advancement of information and communication technology has brought significant opportunities for transforming healthcare services, including pregnancy management through mobile applications. UI (User Interface) and UX (User Experience) design are crucial in ensuring the effectiveness and user satisfaction in the development of such applications. This research employs a Design Thinking approach focused on deep understanding of user needs and preferences. The objective is to design and develop a mobile application specifically for pregnancy management. The study illustrates how Design Thinking can be implemented in healthcare app development, emphasizing the creation of solutions that are effective and relevant to users. The outcomes of this research are expected to contribute to improving healthcare services for pregnant women through mobile technology.